The day the crayons quit (Philomel Books, Penguin Young Readers Group, 2013)
When Duncan arrives at school one morning, he finds a stack of letters, one from each of his crayons, complaining about how he uses them.

The legend of rock paper scissors (Balzer + Bray, HarperCollins, 2017)
You've played the game. Now read the legend of how it all began...Long ago, in an ancient and distant realm called the Kingdom of Backyard, there lived a warrior named ROCK. Meanwhile in the Empire of Mom's Home Office, a second great warrior sought the glory of battle. And his name was PAPER. At the same time, in the Kitchen Realm, in the tiny village of Junk Drawer, lived a third warrior. They called her SCISSORS. These three were the strongest, smartest, and fastest in all the land. Time and again they beat the most fearsome opponents they could find: an apricot, a computer printer--even frozen, breaded, dinosaur-shaped chicken nuggets! But when the warriors finally meet each other, the most epic round of battles begins...and never ends. That is why, to this day, children around the world honor these worthy adversaries by playing ROCK, PAPER, SCISSORS!--Provided by Publisher.

This is MY fort! (Monkey and Cake, ,, 2019)
Monkey and Cake are normally good friends, but today Cake is building a no-Monkey fort--until Monkey teaches him a lesson about being alone and he realizes that forts (and other things) are much better when they are shared.

My tooth is LOST! (Monkey and Cake, ,, 2019)
Monkey is upset because he has lost a tooth, so Cake tries to make him feel better by telling him about the Tooth Fairy--but Monkey just wants his tooth named Kevin.

The day the crayons came home (Penguin Group USA, Philomel Books, an imprint of Penguin Group (USA), 2015)
One day, Duncan is happily coloring with his crayons when a stack of postcards arrives in the mail from his former crayons, each of which has run away or been left behind, and all of which want to come home.

The epic adventures of Huggie and Stick (Philomel Books, Books on Tape, 2018)
When a grumpy stuffed bunny and a happy-go-lucky stick fall out of their boy's backpack, they embark on an odyssey that takes them all around the world, experiencing one crazy adventure after another.

Love from the crayons (Penguin Workshop, 2019)
"Ring in Valentine's Day -- and love -- with the [...] Crayons! This charming new title featur[es] everyone's favorite coloring crew. 'Love is yellow and orange. Because love is sunny and warm. Love is purple. Because it's okay to love outside the lines.' This [...] book, featuring all the The Crayons from The Day the Crayons Quit, explores the bright colors and subtle shades of love." --

Happy St. Patrick's Day from the crayons (Philomel, 2024)
"As St. Patrick's Day fast approaches, Green Crayon would like a break since he's still recovering from Christmas, but when his friends try to take over, it soon becomes apparent just how much he's needed"--

The crayons trick or treat (Philomel Books, an imprint of Penguin Random House, 2022)
"The hilarious crayons from the #1 New York Times bestselling The Day The Crayons Quit are ready to celebrate Halloween! But they don't know what to say when they knock on the door."-- Provided by publisher.

Sleepy, the goodnight buddy (Disney-Hyperion, 2018)
"When a boy who routinely refuses to go to bed gets a talkative stuffed animal, the tables are turned!"--

Happy Easter from the crayons (Philomel, 2023)
Publisher Annotation: Celebrate Easter with a hilarious holiday adventure starring the crayons from the #1 New York Times bestseller The Day the Crayons Quit! Easter is the perfect holiday for crayons! They get to learn new shapes and decorate one giant egg together...but where will they hide it?! Blue Crayon has some ideas...

What is inside THIS box? (Monkey and Cake, ,, 2019)
Monkey has a big box, which he tells Cake has a cat inside, but only when the box is closed; Cake suggest that maybe it is a dinosaur instead, and the two friends puzzle over how they can solve the problem of finding out what is in the box, if it is always empty when opened.

The crayons' book of numbers (Grosset & Dunlap, an imprint of Penguin Random House LLC, 2016)
"Poor Duncan can't catch a break! First, his crayons go on strike. Then, they come back home. Now his favorite colors are missing once again! Can you count up all the crayons that are missing from his box?"--Amazon.

The wrong book (Philomel, 2024)
In this giggle-inducing story, the narrator is WRONG about everything, including that bicycles say cock-a-doodle-doo and firefighters shout Ding Dong! before putting out a fire, until the characters within the book set him straight.

The crayons love our planet (Philomel, 2024)
The hilarious Crayons are back in this celebration of our planet and their contributions to it - white ice caps, green trees, blue oceans and skies, brown soil and even wheat!